Novel Evaluation Systems for Compact In-Wheel Vehicles Considering Deviation of Load Torque between Left and Right Wheel - Son, Seungwan; Song, Changhee; Cha, Suk Won; Lim, Won Sik; Zheng, Chunhua; Xu, Guoqing (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
In-wheel vehicles driven by electrical energy are more efficient and emit less pollutant emissions than conventional vehicles powered by internal combustion engine. However, evaluation system for the in-wheel vehicles is not well established, the absence of the evaluation system for in-wheel vehicles is one of the major obstacles to commercialization of the in-wheel vehicles. In this study, we have suggested a new methodology of dynamometer test for in-wheel vehicle and devised simulators that can analyze the performance of in-wheel vehicles. In general, a new vehicle goes through the performance evaluation on dynamometer test which can simulate a straight motion of vehicles. Due to the characteristics of dynamometer test which simulates only a straight motion, it is not suitable for test for in-wheel vehicle. In the case of in-wheel vehicle, since driving motors on wheels are controlled independently, the stability of in-wheel vehicles during turning is important. Therefore, we have developed an in-wheel vehicle simulator to build a dynamometer test which can simulate turning motions of in-wheel vehicle. Using CarSim & Matlab/Simulink, we realized dynamic motion of a vehicle on a curved 3-demensional road. With this simulator, we could extract the load torque of each wheel during driving on the 3D virtual road. If the derived load torque is applied to motors of dynamometer test, it is possible to simulate driving on real road, through which the performance and the efficiency of in-wheel vehicles can be analyzed before the actual vehicle experiment. Also, we developed another simulator to evaluate the performance and the efficiency of in-wheel vehicles. This simulator allows us to evaluate the performance of in-wheel vehicles by using load torque derived from previous simulator. In this study, we developed two types of simulators to evaluate the performance of in-wheel vehicles in the simulation environment where the load torque for each wheel is different. One simulator derives load torque of each wheel and the other simulator evaluates the performance of in-wheel vehicles.